Application of the Unfolding Model to the Aggression Dimension of the Dimensional Clinical Personality Inventory (IDCP) (2014)
This article compares the suitability of the dominanceand unfolding models for the analysis of theAggressiveness dimension in the IDCP (DimensionalClinical Personality Inventory). The study included975 subjects, with ages ranging from 18 to 81 years(M=29.82, SD=12.28), 58.9% of which were women.The IDCP is composed of 163 items and 12 dimensions;27 items are related to Aggression. The analysiswith the unfolding model indicated the exclusion of15 items due to standard error. Results showed a betterfit for the dominance model. This result may bedue to the nature of the construct, because the itemsassess pathological aspects of personality representingone end of the continuum.